66th Conference on Glass Problems : a collection of papers presented at the 66th Conference on Glass Problems, the University of Illinois at Urbana-Champaign - Conference on Glass Problems (66th : 2006 : Urbana-Champaign, Ill.); Kriven, Waltraud M; American Ceramic Society (Hoboken, NJ : John Wiley & Sons, 2006)
08